Private sector involvement and international financial crises : an analytical perspective - Chui, Michael; Gai, Prasanna, 1969- (Oxford ; New York : Oxford University Press, 2005)
This book integrates analyses of sovereign debt and crises in financial markets. Issues examined include the design of sovereign bankruptcy procedures, and the role of the IMF in influencing creditors and debtor countries
Includes bibliographical references (p. [195]-204) and index.
aia 15/05/13
Loan
Keywords: Financial crises; International finance